2008
DOI: 10.1158/0008-5472.can-08-1209
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Induction of Colonic Tumors in a Mouse Model of Sporadic Colon Cancer

Abstract: A defined rodent ''new Western diet'' (NWD), which recapitulates intake levels of nutrients that are major dietary risk factors for human colon cancer, induced colonic tumors when fed to wild-type C57Bl/6 mice for 1.5 to 2 years from age 6 weeks (two-thirds of their life span). Colonic tumors were prevented by elevating dietary calcium and vitamin D 3 to levels comparable with upper levels consumed by humans, but tumorigenesis was not altered by similarly increasing folate, choline, methionine, or fiber, each … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
102
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 40 publications
5
102
1
Order By: Relevance
“…Dietary components such as red meat are known risk factors for colorectal carcinoma 3,14,15 , but it is not known how diet makes a footprint on gut microbes associated with or even causing colorectal carcinoma. We assessed influence of a number of clinical or lifestyle factors on gut microbial genes or MLGs, and found that the control, adenoma or carcinoma state was indeed among the strongest factors ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary components such as red meat are known risk factors for colorectal carcinoma 3,14,15 , but it is not known how diet makes a footprint on gut microbes associated with or even causing colorectal carcinoma. We assessed influence of a number of clinical or lifestyle factors on gut microbial genes or MLGs, and found that the control, adenoma or carcinoma state was indeed among the strongest factors ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear, however, whether more bacteria or archaea serve as markers for, or contribute to the aetiology of, colorectal carcinomas. Moreover, as perhaps the most important environmental factor for human health, or our 'other genome' 12,13 , it remains to be explored whether and how the gut microbiome integrate other risk factors, for example, diet, smoking, obesity [1][2][3]14,15 and generate a coherent signal for colorectal carcinogenesis.…”
mentioning
confidence: 99%
“…sporadic | colon cancer | Western diet | microarray B oth large and small intestinal tumors develop in WT C57BL/6 mice after long-term (1.5-2 y) feeding of a fully defined Western-style diet that combines a number of risk factors for human colon cancer (NWD1: higher fat, lower calcium, vitamin D 3 , donors to the single carbon pool, and fiber, and carbohydrate supplied by sucrose, a refined sugar commonly consumed in developed but not undeveloped countries) (1,2). These dietaryinduced tumors arise with an incidence, frequency, and lag (i.e., two-thirds of the host lifespan) similar to those of human colon tumors, making them a useful model of sporadic intestinal cancer, the form of the disease responsible for >90% of intestinal cancer in the human (1,2).…”
mentioning
confidence: 99%
“…These dietaryinduced tumors arise with an incidence, frequency, and lag (i.e., two-thirds of the host lifespan) similar to those of human colon tumors, making them a useful model of sporadic intestinal cancer, the form of the disease responsible for >90% of intestinal cancer in the human (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation